2015
DOI: 10.1099/jgv.0.000245
|View full text |Cite
|
Sign up to set email alerts
|

Visualization and quantification of simian immunodeficiency virus-infected cells using non-invasive molecular imaging

Abstract: In vivo imaging can provide real-time information and three-dimensional (3D) non-invasive images of deep tissues and organs, including the brain, whilst allowing longitudinal observation of the same animals, thus eliminating potential variation between subjects. Current in vivo imaging technologies, such as magnetic resonance imaging (MRI), positron emission tomography-computed tomography (PET-CT) and bioluminescence imaging (BLI), can be used to pinpoint the spatial location of target cells, which is urgently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…The EcoHIV-eLuc reporter was selected because (1) it contains all the components needed for HIV-1 replication except for the HIV Env, (2) convenient to be handled at biosafety level II containers due to Env deletion and (3) bioluminescence is more sensitive than fluorescence and the eLuc reporter can be used to detect less than 10 single cells[38]. We chose the HEK293T cell line because of the high transfection efficiency with the cost-effective calcium phosphate precipitation method.…”
Section: Resultsmentioning
confidence: 99%
“…The EcoHIV-eLuc reporter was selected because (1) it contains all the components needed for HIV-1 replication except for the HIV Env, (2) convenient to be handled at biosafety level II containers due to Env deletion and (3) bioluminescence is more sensitive than fluorescence and the eLuc reporter can be used to detect less than 10 single cells[38]. We chose the HEK293T cell line because of the high transfection efficiency with the cost-effective calcium phosphate precipitation method.…”
Section: Resultsmentioning
confidence: 99%
“…It has been explored previously to image immune cell (such as CD4 T+ cells, CD8 T+ cells, and Mac1+ cells) location and homing in the central nervous system of mice with superparamagnetic antibodies (51). Molecular imaging has been successfully applied to visualize simian immunodeficiency virus (SIV)-infected cells in the body of rodent models of HIV (52). Like human, lymph nodes are located throughout the whole body of a macaque monkey.…”
Section: Discussionmentioning
confidence: 99%
“…Complementary to these imaging studies, use of laser capture microdissection revealed a compartmentalization of viral sequences in brain from animals infected with a neurotropic virus ( 109 ). In addition to tissue imaging assays, MRI-based methodologies have been widely used for the study of HIV/SIV neuropahtogenesis ( 110 113 ) as well as the in vivo viral dynamics in the brain of experimental models ( 17 ).…”
Section: What Can We Learn From Hiv/siv Infections?mentioning
confidence: 99%
“…Today, several imaging technologies and platforms are available for tissue analysis. Several factors should be taken into consideration regarding the choice of the most relevant platform, including the following: The scientific question under investigation: tissue cell composition and viral reservoirs [light microscopy, confocal microscopy, ion beam imaging ( 126 ), Laser Capture Microdissection ( 127 )], subcellular structure and virus–host protein interactions (confocal microscopy, electron microscopy, high-resolution optical imaging technologies), or assessment of cellular and viral dynamics at organ or whole-body level [MRI ( 17 ), PET scan ( 123 ), confocal endoscopy]. The requirement for high-resolution, “volumetric” analysis or live imaging (two-photon microscopy) to address the biological process under investigation.…”
Section: What Can We Learn From Hiv/siv Infections?mentioning
confidence: 99%
See 1 more Smart Citation